(untitled) (Asian Journal of Ethnobiology, 2023)
Abstract. Abadi BRH, Neinhuis C, Safaeian R, Lautenschläger T. 2023. Ethnobotanical studies of plant resources of Taftan Mountain, Sistan and Baluchestan in southeastern region of Iran. Asian J Ethnobiol 6: 75-117. Due to poverty, lack of proper access to cities, the inadequacy of health services, and the availability of indigenous remedies, plant usage still is an important part of the cultural heritage in Baluchestan, Iran. Our study was conducted between 2018 and 2020 in Taftan Mountain area to report the traditional uses of the endemic plant species. During 40 field trips, 54 informants were interviewed. Totally, 3199 citations and 102 species belonging to 43 families were reported. Medical purposes comprised 75% of citations and 25% were referred to non-medical purposes. Medicinal plants were used against 178 disorders, and decoction was the most commonly applied method of preparation. Leaves were the most frequently used plant parts. Although most recorded species belong to Apiaceae, Asteraceae, and Lamiaceae, most citations belong to Lamiaceae followed by Asteraceae and Apiaceae. Most of the local people in the area still use the plants especially for treating their ailments. Women contributed more than men to the citations. The highest values for the ethnobotanical indices RFC and CI were recorded for Pistacia atlantica Desf., while the diseases brucellosis, callus, and eye infection had the highest FIC-value (1). Information regarding traditional knowledge is limited to elders; therefore, it needs to be recorded and saved for future generations.